Consejería nutricional y prácticas de alimentación complementaria en madres con niños lactantes atendidos en un establecimiento de salud Iquitos 2022 - Panduro Alva, Maria Ximena (2025)
The objective was to determine the relationship between Nutritional Counseling and Complementary Feeding Practices in mothers with breastfeeding children (6 to 23 months), from the 6 de Octubre health facility, Iquitos 2022. It is a quantitative, non-experimental, descriptive, cross-sectional and correlational study; the population made up of 60 mothers. The technique used was the survey and instruments: a checklist on nutritional counseling (validity 87.50%, reliability 81.5%) and a questionnaire on complementary feeding practices with validity 86.25% and reliability of 6 - 8 months (73.8%), 9 - 11 months (79.7%) and 12 months or more (79.7%). The results obtained were: 70.0% presented inadequate nutritional counseling and 30.0% adequate. Regarding complementary feeding practices, 65.0% stated that they were incorrect and 35.0% correct. When relating both variables, an X2=4.776 was obtained; p=0.029 < α=0.05. It is concluded that there is significance between nutritional counseling and complementary feeding practices in mothers with breastfeeding children (6 to 23 months) of the 6 de Octubre health facility.